Room temperature exciton–polariton Bose–Einstein condensation in organic single-crystal microribbon cavities - Ji Tang (Nature Portfolio, 2021)
The use of room temperature exciton–polariton Bose–Einstein condensation is limited by the need for external high-finesse microcavities. The authors generate room temperature EPs with single-crystal microribbons as waveguide Fabry–Pérot microcavities, and demonstrate controllable output of coherent light.